2016
DOI: 10.1108/cdi-10-2015-0130
|View full text |Cite
|
Sign up to set email alerts
|

Personality and occupational specialty

Abstract: The purpose of this study was to reexamine the role of personality in occupational specialty choice, to better understand how and in what ways personality traits might influence vocational development after a person has chosen a career. Design/Methodology/Approach: The study tested hypotheses in a sample of UK medical students, each of whom had chosen their specialty pathway, and completed a measure of the Big Five personality traits. Associations of the junior doctor's Big Five personality traits with the Hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…One study identified all medical disciplines to be throughout 'investigativesocial' (Borges et al, 2004), whereas another study by Petrides and McManus (2004) revealed that e.g., surgery is rather a 'realistic' discipline (including people who like to work with things: here hands and tools, needing high levels of technical proficiency, craftsmanship and practical skills), internal medicine can be more assigned to the 'investigative' category (including people who like to work with data: exploring symptoms and relating them to latent causes to make a diagnosis), and psychiatry was considered to be more 'artistic' (including people who like to work with ideas: interpreting patients' problems using various bio-psycho-social theories and responding individually to each patient). In turn, physicians who selected specialties with more pronounced social features also had higher scores on the Big Five dimension of 'agreeableness, ' whereas higher 'neuroticism' implied rather a preference for 'artistic' and an aversion for 'realistic' or 'enterprising' specialties (Woods et al, 2016). Overall, two meta-analyses found three moderate relationships between personality traits (Big Five) and vocational interests (RIASEC) of medical students (see Duffy et al, 2009): 'extraversion' with 'enterprising' and 'social, ' and 'openness to experience' with 'artistic.'…”
Section: Virtues and Character Strengths In The Literaturementioning
confidence: 95%
“…One study identified all medical disciplines to be throughout 'investigativesocial' (Borges et al, 2004), whereas another study by Petrides and McManus (2004) revealed that e.g., surgery is rather a 'realistic' discipline (including people who like to work with things: here hands and tools, needing high levels of technical proficiency, craftsmanship and practical skills), internal medicine can be more assigned to the 'investigative' category (including people who like to work with data: exploring symptoms and relating them to latent causes to make a diagnosis), and psychiatry was considered to be more 'artistic' (including people who like to work with ideas: interpreting patients' problems using various bio-psycho-social theories and responding individually to each patient). In turn, physicians who selected specialties with more pronounced social features also had higher scores on the Big Five dimension of 'agreeableness, ' whereas higher 'neuroticism' implied rather a preference for 'artistic' and an aversion for 'realistic' or 'enterprising' specialties (Woods et al, 2016). Overall, two meta-analyses found three moderate relationships between personality traits (Big Five) and vocational interests (RIASEC) of medical students (see Duffy et al, 2009): 'extraversion' with 'enterprising' and 'social, ' and 'openness to experience' with 'artistic.'…”
Section: Virtues and Character Strengths In The Literaturementioning
confidence: 95%
“…Many specialty-related organizational, professional and individual factors, such as employment sector, clinical patient contact, and work style preferences, have been found to contribute to physicians' career choice [1][2][3][4][5][6] and well-being at work. 3,[7][8][9][10][11][12] From individual-level psychological factors, personality traits 13 have been suggested to be among the most important determinants of workrelated well-being.…”
Section: Introductionmentioning
confidence: 99%
“…However, at least two different arguments can be put forward which suggest that this crystallisation process leads to associations between specifi c types of educational and occupational expectations and specifi c types of fertility expectations. The fi rst argument for their interconnectedness is based on gender role theory (Stockard 2006; Risman/Davis 2013), the second one on ideas about the development of personality and social orientation among adolescents (Woods et al 2016;Tavares 2016). We will discuss both arguments in turn.…”
Section: Theorymentioning
confidence: 99%
“…Personality characteristics have been found to be related to fertility outcomes (Jokela 2012; Skirbekk/Blekesaune 2014; Tavares 2016), choice of educational fi eld (Korpershoek et al 2010), and occupational choices (Wells et al 2016;Woods et al 2016). A high score on agreeableness, for instance, is related to a higher propensity to have children (Jokela 2012; Tavares 2016, but not Skirbekk/ Blekesaune 2012), a low propensity to opt for educational tracks in science and economics (Korpershoek et al 2010) and a lower propensity to opt for managerialtype occupations (Wells et al 2016) and a higher propensity to opt for health care specialties that emphasize social interaction (Woods et al 2016). Thus, adolescent girls who score high on agreeableness might be expected to be strongly oriented towards care and social interaction, and thus to be attracted both to caring for children and to fi elds of study and occupation in which care and social interaction are central.…”
Section: Theorymentioning
confidence: 99%